PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI MIPA SMA NEGERI 6 PADANG - Hayyu, Mutiara (Departemen Matematika, 2023)
In school, math communication skills are very important. This study focuses on these skills. The assessment of the XI MIPA class of SMA Negeri 6 Padang shows that students' ability in this area still needs to be improved. Problem-based learning (PBL) can help in this regard. This study examines the advantages of these skills in PBL compared to traditional methods. The study used Quasi Experiment with Posttest-Only Control Group Design and simple random sampling. In the hypothesis test, the P-value of 0.000 rejected the null hypothesis (H0). This shows that PBL outperforms traditional learning.Keywords– Problem Based Learning Model, Mathematical Comuunication Ability, Quasi Experiment